2011
DOI: 10.2478/v10153-011-0064-z
|View full text |Cite
|
Sign up to set email alerts
|

Macular thickness measurements in healthy eyes using spectral optical coherence tomography

Abstract: AIM: The aim of the present study was to measure macular thickness in healthy eyes and find whether it changes with age. MATERIAL AND METHODS: We examined 163 healthy eyes of 84 healthy volunteers. In order to measure their macular thickness the patients were examined using spectral-domain optical coherent tomography (SD-ОСТ - iVue, Optovue). They were allocated into 6 age groups. RESULTS: The mean central macular thickness (inner circle - fovea centralis) was 248.9 ± 17.9 μm (mean ± SD), and the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
4
6
0
2
Order By: Relevance
“…18,22 The temporal and nasal quadrants were thinnest and thickest, respectively, for the outer macular (perifoveal) region (Table 2), which is consistent with the arrangement of fibres in the papillo-macular region. 23 We found that the BMI was positively correlated with macular thicknesses (Table 3). The association between obesity and diabetes mellitus (DM), particularly type 2 (non-insulin-dependent) DM, has been known for several hundred years.…”
Section: Discussionmentioning
confidence: 72%
“…18,22 The temporal and nasal quadrants were thinnest and thickest, respectively, for the outer macular (perifoveal) region (Table 2), which is consistent with the arrangement of fibres in the papillo-macular region. 23 We found that the BMI was positively correlated with macular thicknesses (Table 3). The association between obesity and diabetes mellitus (DM), particularly type 2 (non-insulin-dependent) DM, has been known for several hundred years.…”
Section: Discussionmentioning
confidence: 72%
“…7,9 Significant differences in the macular central subfield thickness (CST) have been reported in healthy subjects among different races, genders, and age groups; many differences were also found between several scan protocols and OCT units. 6,8,[10][11][12][13][14][15][16][17][18][19][20] Normative macular thickness values using different OCT units on a specific population are needed to identify reference values for many eye conditions. A normative database for macular thickness helps us determine if a patient falls within or outside normal values for his age and race; in a clinical research setting, this database would help us determine a patient's inclusion or exclusion criteria, additionally, if the treatment is meant to decrease macular thickness, we need to be sure that we have an abnormally thick retina at the beginning in order to adequately measure its variations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported normative data of macular thickness using various commercially available SDOCTs 4–12 . The macular thickness measurement for diagnostic function may differ with the population which is used as a database as well as the instrument which is being used.…”
Section: Introductionmentioning
confidence: 99%